4c+9=((8c+1)-(2c-11))/3

Simple and best practice solution for 4c+9=((8c+1)-(2c-11))/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c+9=((8c+1)-(2c-11))/3 equation:



4c+9=((8c+1)-(2c-11))/3
We move all terms to the left:
4c+9-(((8c+1)-(2c-11))/3)=0
We multiply all the terms by the denominator
4c*3)-(((8c+1)-(2c-11))+9*3)=0
We add all the numbers together, and all the variables
4c*3)-(((8c+1)-(2c-11))=0
Wy multiply elements
12c^2=0
a = 12; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·12·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:
$c=\frac{-b}{2a}=\frac{0}{24}=0$

See similar equations:

| 3(x-5)-5(x-3)=x+8-(x-8) | | x/4+10=1/8 | | 5/6y-1/6=7/6 | | 9y-7=13y+5 | | -16x^2+12x+52=0 | | 14x+16=2(5x+3) | | F(x)=(8x-3)(2x+7) | | 7=2m+5 | | (y+7)^2-49=0 | | 94=2n(-3n) | | (y+7)2-49=0 | | (x)^2+(x+3)^2=5 | | -2x+7=1x-9 | | -9n-8=-10n+-7 | | (x-0)^2+(x+3)^2=5 | | -2x+9=X+7 | | -8x+2=4(x+4) | | 5(2x-1)=14+3(x-2) | | -377=x-1,000 | | 6+3/5x=7/10x | | -8x+7=4(x-6) | | 6+35b=710b | | 30+59.45x=64.45x | | 3(x+3x)=12 | | 3.1(13.5r-5.3)=91.8 | | 6x-4=3(-x+2) | | 2x-4=3(-x+2) | | r/2+6=-8 | | -4(-2y–7)=12y+4 | | 5x-2=4(-x+3) | | 105=-12n(-5n) | | 2x-12=3(-x+4) |

Equations solver categories